Impact of the genetic background on plasmid-borne antibiotic resistance: Supplemental information - Jagdmann, Jennifer (Uppsala University, 2022)
Data consists of tables for the article "Impact of the genetic background on plasmid-borne antibiotic resistance".

The dataset was originally published in DiVA and moved to SND in 2024.

Data består av tabeller för artikeln "Impact of the genetic background on plasmid-borne antibiotic resistance".

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Impact of the genetic background on plasmid-borne antibiotic resistance: Supplemental information
Keywords: drug resistance; läkemedelsresistens; plasmids; plasmider; genetic factors; genetiska faktorer; antibiotic resistance; antibiotikaresistens; Microbiology; Mikrobiologi